Gestão Social em Empreendimentos Econômicos Solidários: uma abordagem no Oeste Potiguar - Dias, Thiago Ferreira (2011)
The central research question was to search for data to ratify the theory and discourse of the so-called practitioners of economic solidarity, by defending the substantive rationality should guide the principles of economic solidary, designing the space economy incidental and not the primacy of relations in determining social as well, reflecting the predominance of dimensions of social management in administrative practices of ESS's. For both analyzed the theoretical dimensions of social management - sociopolitical, economic, organizational and environmental - manifested in organizational practices supportive of economic organization Potiguar West. For the success of the research realized the triangulation involving a combination of quantitative and qualitative methodological approaches. At first the research will use a quantitative approach, from the cluster analysis, to verify the behavior of the sample chosen for this study. In the second stage of the qualitative study was carried out focus group technique (FLICK, 2002) for further analysis of the dimensions of social management on organizational practices supportive of economic organization, related to the principles of Solidary Economy, established in a quantitative approach. In quantitative analysis, the socio-political dimension, it was clear that the more equity instruments of internal and external, from the purposeful living in public spaces, the best monetary results. Another point worth stressing concerns the economic dimension, with the practice reciprocity prevailing in market. Thus, the qualitative approach was possible to understand the processes of exchange of product or service. Rural enterprises surveyed in the allocation of the agro-ecological products have the following scale of priority, sequentially: self-consumption (domestic), market and exchange. The research leads to the fact that training and practices that enhance the socio-political dimension (knowledge, empowerment, sense of belonging) become the guiding principle for the strengthening of the social management in the context of other dimensions, leading to gains sociopolitical, economic, organizational and environmental. Despite the weaknesses found in the organizational dimension and environment, both in a quantitative as in qualitative, we determined that the practices of ESS's Potiguar West incorporate predominantly elements of social management and economic solidarity, with a preponderance of substantive rationality in the primacy of the instrumental. Finally, research has brought information that the participants of the ESS's do not give the money economy primacy in determining social relations, which in turn leads to the confirmation that, in practice the solidarity economy, prevailing the dominance of substantive rationality, as a guide for organizational practices